Factors related to mouth breathing syndrome in preschool children and the effects of incompetent lip seal: An exploratory study. Issue 6 (15th September 2022) - Inada, Emi; Saitoh, Issei; Kaihara, Yasutaka; Murakami, Daisuke; Nogami, Yukiko; Kiyokawa, Yuki; Tanaka, Reira; Sakata, Kensuke; Yamasaki, Youichi
Abstract: Objectives: A set of orofacial signs and symptoms completely or partially present in individuals who replace the correct pattern of nasal breathing with an oral or mixed pattern is defined as mouth breathing syndrome (MBS). In a previous report, it was clarified that an incompetent lip seal (ILS) affected the occurrence of MBS among primary school children. However, the factors related to MBS and the effect of ILS in preschool children remain unclear. The purpose of this study was to clarify the factors relevant to MBS in preschool children and investigate the relationship of ILS to MBS. Material and Methods: We surveyed 285 preschool children between 3 and 5 years of age. Their guardians completed the questionnaire, which consisted of 44 questions regarding the children's daily health conditions and lifestyle habits. To classify the closely related questions into their respective factors and to examine the strength of the correlation between the newly revealed factors, an exploratory factor analysis with promax rotation was performed. Results: The factor analysis identified nine items representing four factors. Factors 1–4 were defined as "diseases of the nose, " "ILS, " "problem with swallowing and chewing, " and "eating and drinking habits, " respectively. Factor 2 most strongly correlated with Factor 1, and both Factors showed a relatively strong correlation with Factor 3. Conclusions: The initial stage of MBS may be present in preschool children. ILS and diseases of the nose can cause poor development of oral functions, such as breathing and eating.